Enhanced electrochemical performance of Li4Ti5O12 anode material by LaF3 surface modification for lithium-ion batteries. (October 2022) - Wei, Aijia; Mu, Jinping; He, Rui; Bai, Xue; Li, Xiaohui; Zhang, Lihui; Zhang, Xi; Wang, Yanji; Liu, Zhenfa
Abstract: The LaF3 -modified Li4 Ti5 O12 materials have been synthesized via a chemical co-precipitation method, and the effects of different amounts of LaF3 modification (0.5 wt%, 1 wt%, 2 wt%, and 3 wt%) on the morphology, structure, and electrochemical performance of the Li4 Ti5 O12 (LTO) materials were investigated. X-ray diffraction and X-ray photoelectron spectroscopy (XPS) characterizations show that the La 3+ or F − ions are not incorporated into the LTO particles, and major LaF3 and minor La2 O3 peaks are observed in the LaF3 -modified LTO samples. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images show that the generated LaF3 /La2 O3 nanoparticles are continuously wrapped around the surfaces of LTO particles. Charge-discharge tests reveal that the 1 wt% LaF3 -modified LTO material (1LaFLTO) exhibits the highest rate capacity values among all of the samples of 199.9, 187.4 and 159.7 mAh g −1  at 3C, 5C, and 10C, respectively between 0 and 3 V. Moreover, 1LaFLTO also delivers superior cycling stability with a capacity retention of 94.5% after 300 cycles at 5C between 1 and 3 V. The electrochemical results demonstrate that the appropriate LaF3 /La2 O3 nanoparticles coated on the surface of 1LaFLTO particles not only reduce electrode polarization, SEI film resistance, and charge-transfer resistance but also accelerate Li + diffusion and improve the reversibility, which is favorable for enhancing the electrochemical performance of LTO material. Highlights: The LaF3 -modified LTO materials were synthesized via a chemical co-precipitation method. The LaF3 /La2 O3 nanoparticles were generated and former a continuous coating layer on the surface of LTO, which could suppress electrolyte decomposition, reduce the side-reactions at the LTO/electrolyte interfaces, and improve the structural stability of LTO material. The 1 wt% LaF3 -modified LTO material exhibited the highest rate capacity and cycling stability among all of the samples at voltages of 0–3 V and 1–3 V. The enhanced electrochemical performance of 1 wt% LaF3 -modified LTO was ascribed to a higher Li + diffusion coefficient and a lower electrode polarization, SEI film resistance, and charge-transfer resistance after an appropriate amount of LaF3 /La2 O3 formed as a conductive medium coating on the surface of LTO.